1996
DOI: 10.1093/ndt/11.3.461
|View full text |Cite
|
Sign up to set email alerts
|

Proteinuria and blood pressure as causal components of progression to end-stage renal failure

Abstract: Only primary renal disease and proteinuria were related to renal survival, being baseline plasma creatinine confounding factor. By blocking the possible causal role of proteinuria and hypertension, end-stage renal failure could be prevented in a significant percentage of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(58 citation statements)
references
References 11 publications
2
54
1
1
Order By: Relevance
“…High BP is a known independent risk factor for faster decline of GFR (22)(23)(24). Consistent with these findings, we found that higher SBP (.157 mmHg) and DBP (.80 mmHg) were associated with progression to long-term dialysis.…”
Section: Discussionsupporting
confidence: 88%
“…High BP is a known independent risk factor for faster decline of GFR (22)(23)(24). Consistent with these findings, we found that higher SBP (.157 mmHg) and DBP (.80 mmHg) were associated with progression to long-term dialysis.…”
Section: Discussionsupporting
confidence: 88%
“…In adults, HTN is an independent risk factor for CKD progression (159)(160)(161) and also in a large prospective study of children with CKD SBP greater than 120 mmHg has been associated with a faster decline of GFR (162).…”
Section: Chronic Kidney Disease and Renal Insufficiencymentioning
confidence: 94%
“…CKD is also related to a decrease in quality of life and cognitive function (2). Hypertension and proteinuria promote CKD progression and increase the risk of CVD and mortality (3). Blockade of the reninangiotensin-aldosterone system (RAAS) is well known to reduce urinary albumin excretion, and it is considered a mainstay of therapy in the prevention of ESRD (4,5).…”
Section: Introductionmentioning
confidence: 99%